Physical and sensory quality of Coffea arabica L. variety Colombia variety, Nespresso AAA profile, in the Union, Nariño - Ramos V., Lady Johanna; Criollo E., Hernando (Revista de Ciencias Agrícolas, 2017)
In response to the need of generating alternatives to ensure the quality and differentiation of the Nariño coffee, this work was carried out with the objective of evaluating the physical and sensory quality of coffee variety Colombia, red fruit, sown to full sunlight by growers of Nespresso AAA program 2015, growing at different altitudes with variations in the coffee post-harvest, in the municipality of La Union, Nariño. Ten kilos of coffee fruit were harvested per farm; these fruits were processed through wet benefit and dried under different solar exposure times, and then were carried to the Almacafé laboratory to assess their physical and organoleptic characteristics such as: aroma, fragrance, acidity, body, taste, residual flavor, balance, clean cup, sweetness and score of taster. It was also analyzed the relationships between climatic and agronomic factors in each farm with the cup quality. The data were analyzed by multivariate analysis of principal components (PCA) and multiple correspondence analyses (ACM). The altitudes are not particularly associated with the quality parameters of the coffee drink; lower contents of P, less time of fermentation (16 - 17h) and drying (20 - 25h of sun), were associated with higher scores of quality. The complex interaction of all the variables associated to the coffee production of, is what defines, the cup quality.